Non-Alignment to Strategic Autonomy - Jakub Zajączkowski; Manish Jung Pulami (Politeja)
This paper explores India’s strategic positioning vis-à-vis the liberal international order (LIO), examining how India has historically both engaged with and asserted autonomy from the Western-led order. It argues that India’s evolving foreign policy—from Nehru’s non-alignment to Modi’s strategic autonomy—reflects a deliberate use of specific approaches to create space within the LIO for its unique national interests. The main argument of the paper is that India’s engagement with the LIO has not involved wholesale rejection of the extant LIO framework but rather the selective leveraging and reimagining of liberal principles to preserve India’s strategic interests while promoting a multipolar, more inclusive global order. India’s approach to the LIO from its independence to now has been marked by continuity. Since 1947, India has sought to uphold sovereignty while benefiting from liberal principles, particularly in institutional and economic domains. The paper draws on the theoretical framework of defensive realism and institutional neoliberalism to deconstruct and highlight India’s policy approach to the LIO, which is characterized by pragmatism and suggests that India could be described as a transactional power.